Antifungal potential of multi-drug-resistant Pseudomonas aeruginosa: harnessing pyocyanin for candida growth inhibition - Oves, Mohammad; Khan, Mohd Shahnawaz; Al-Shaeri, Majed; Khan, Mohammad Saghir (Frontiers in Cellular and Infection Microbiology, 2024)
Pseudomonas aeruginosa, known for its multidrug resistance and role in hospital-acquired infections, was the focus of a study involving 20 bacterial strains isolated from soil samples near the Hindan River in Ghaziabad, India. These isolates were subjected to biochemical and morphological analyses, revealing a predominance of bacteria from the genus Pseudomonas. Notably, most strains produced exopolysaccharides. This study's critical finding was identifying the strain GZB16/CEES1 as exhibiting exceptional drug resistance and pyocyanin production. More biochemical and molecular analysis was done on this strain, which included taking out and submitting its 16S rRNA gene sequence to the EMBL gene bank (accession number LN735036.1). GZB16/CEES1 showed 100% resistance to various antibiotics. The plasmid-curing assays revealed an intriguing fact: most resistance genes appeared to be plasmid-based. The size of the plasmid in GZB16/CEES1 was estimated to be approximately 24 kb based on standard ladder comparisons. The ability of P. aeruginosa to produce pyocyanin was the main focus of this research. This was further explored through plasmid-curing studies. The study highlighted the anticandidal activity of the strain, which is closely linked to pyocyanin production. The bacterial extract's minimum inhibitory concentration (MIC) against Candida albicans was 50 µg/ml, with a slightly lower pyocyanin-based MIC of 38.5 µg/ml. A significant aspect of this study revealed through scanning electron microscopy, was the direct interaction between the bacterial strains and Candida albicans cells, leading to the latter's destruction of cells. This finding underscores the potential of P. aeruginosa in understanding microbial interactions and developing new strategies to combat fungal infections.